REPRESENTASI FEMINISME PENERIMAAN DIRI DALAM VIDEO KLIP LAGU TUTUR BATIN - Cut Nalda Sari; Maimunah Br Nasution; Hasan Sazali; Maulana Andinata Dalimunthe (Lembaga Pengembangan Kinerja Dosen, 2023)
This research was conducted to find out the message to be conveyed by the lyrics and music video Tutur Batin by author Yura Yunita. Pop vocalist Yura Yunita has hit the Indonesian music scene since childhood. One of the songs written and performed by Yura Yunita is called Inner Speech and features her singing. This is what interests academics to conduct a more in-depth analysis of the music video for the song Tutur Batin. By breaking the video clips into various scenes related to the representation of feminism and categorizing them according to Barthes's view system which includes denotative meaning, connotative meaning, and myth, the analysis technique used in this research is data analysis using Roland Barthes semiotics. The research findings show that the videos depict strong women who can express themselves by being themselves. She had the choice to be like other women in society's eyes, but she chose to be herself. This is the same as the principle of self-acceptance feminism, which states that in order for women to live as equals in society, they must have the freedom to express themselves however they choose.